Characterization of human immunodeficiency virus type 2 envelope glycoproteins: dimerization of the glycoprotein precursor during processing. - Rey, M A (1989)
Four glycoproteins with apparent molecular weights of 300,000, 140,000, 125,000, and 36,000 (gp300, gp140, gp125, and gp36) were detectable in human immunodeficiency virus type 2 (HIV-2)-infected cells. gp125 and gp36 are the external and transmembrane components, respectively, of the envelope glycoproteins of HIV-2 mature virions. gp300 and gp140 are only detectable in virus-infected cells. They have identical isoelectric points, suggesting that gp300 might be a dimeric form of the immature precursor, gp140. The purified gp300 can be dissociated in a slightly acidic buffer to give rise to monomers of 140,000 molecular weight. Such dissociated monomers and the purified gp140 showed identical patterns of polypeptides after partial proteolysis with Staphylococcus aureus V8 protease. Pulse-chase experiments indicated that gp300 is formed after synthesis of gp140 and before the detection of the mature external envelope glycoprotein, gp125. These results were confirmed by using various inhibitors of glycosylation and inhibitors of trimming enzymes. Dimer formation of the envelope glycoprotein precursor was also observed in cells infected with simian immunodeficiency virus (SIV), a virus closely related to HIV-2. On the other hand, the envelope glycoprotein precursor of HIV-1 did not form a dimer during its processing. Therefore, dimer formation seems to be a specific property of HIV-2 and SIV envelope gene expression. Such transient dimerization of the glycoprotein precursor might be required for its efficient transport to the Golgi apparatus and for its processing.